My kind of happy - Bramley, Cathy (Orion, 2021)
"Flowers have always made Fearne smile. She treasures the memories of her beloved grandmother's floristry and helping her to arrange beautiful blooms that brought such joy to their recipients. But ever since a family tragedy a year ago, Fearne has been searching for her own contentment. When a chance discovery inspires her to start a happiness list, it seems that Fearne might just have found her answer... Sometimes the scariest path can be the most rewarding. So is Fearne ready to take the risk and step into the unknown? And what kind of happiness might she find if she does?"--Publisher.